The Islamization of the Gig Economy Concept - Khoirul Umam; Farid Khairi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to explore the integration of Islamic values ​​into the gig economy—a sector that expanded rapidly during the pandemic while facing challenges regarding social protection and worker exploitation. A qualitative method with a descriptive approach was employed to analyze the phenomena experienced by gig workers. The research proceeded in three stages: *de-Westernization* to identify secular elements within gig economy practices; *integration* to infuse the system with Islamic values ​​such as justice and responsibility; and *Islamization* to propose concrete modifications for creating a fairer and more sustainable system. The findings indicate that applying Islamic principles can address existing challenges, such as inequitable profit distribution and inadequate worker protection. By adopting values ​​like social solidarity and environmental responsibility, the gig economy can transform into an economic mechanism that not only benefits individuals but also prioritizes the well-being of society as a whole. This study highlights the importance of reforming policies and practices to ensure the gig economy operates in alignment with Islamic values, thereby fostering a more just and sustainable economic ecosystem.